Confronting the "Racist Demon": Renegotiating South African Domestic Entitlement in Aotearoa/New Zealand - Geyer, Kayleigh; Kahu, Ella; Tuffin , Keith (New Zealand Sociology, 2022)
The employment of Black women as maids in White South African households is common in the post-apartheid nation. When questioned outside of the discursive structures that sustain its functioning, this domestic labour arrangement is revealed as one deeply rooted in relations of power, oppression and privilege. The mass wave of South African emigrants to other White ‘homelands’ following the fall of apartheid, alongside their abrupt confrontation with a new social normality, promotes questioning into how they account for the differences in domestic labour between South Africa and Aotearoa/New Zealand. Using Foucauldian discourse analysis, the accounts of eight White South African immigrants are deconstructed. The four discourses of ‘invisible Whiteness’,‘gendered domestic work’, ‘more equal’ and ‘lifting the veil’ give insight into how White South Africans negotiate historical indoctrination and contemporary White identity. In exploring White South African immigrants’ accounts of domestic labour relations, which are inconsistent with everyday life in Aotearoa/New Zealand, this research contributes to an understanding of how oppressive cultural normalisations can be reflected on and renegotiated following emigration.